1364. Effect of Cefepime Prophylaxis on Bacterial Bloodstream Infections in Neutropenic Patients with Acute Myelogenous Leukemia. (31st December 2020) - Dassner, Aimee; Almatrafi, Mohammed; Slone, Tamra; Aquino, Victor M; Sebert, Michael
Abstract: Background: Bacteremia is a major cause of morbidity and mortality among children with acute myelogenous leukemia (AML) and chemotherapy-induced neutropenia. Data evaluating the utility of bacterial prophylaxis in this pediatric population are limited. In April 2014, Children's Health (CH) implemented the use of cefepime bacterial prophylaxis for AML patients undergoing induction and intensification chemotherapy. The objective of this study was to evaluate the impact of this practice on the frequency of documented bacterial bloodstream infections (BSIs). Methods: This was an observational, retrospective cohort study of patients < 21 years of age with AML admitted at CH from January 2010 through December 2018. The primary outcome was frequency of documented BSIs before (PRE; Jan 2010 to Mar 2014) and after (POST; Apr 2014 to Dec 2018) implementation of routine bacterial prophylaxis. Secondary outcomes included differences in total antibiotic days per neutropenia days and the occurrence of neutropenia-associated C. difficile infection between groups. Results: Of 90 patients with AML who met the cohort inclusion criteria, 38 and 52 were treated during the PRE and POST prophylaxis periods, respectively. The incidence rate of documented BSIs per 1000 neutropenia days decreased from 15.5 to 2.8 after the implementation of routine cefepime prophylaxis (incidence rate ratio 0.18, Poisson regression 95% CI 0.09 to 0.33, P < 0.001). Patients were more likely to have febrile neutropenia in the PRE group (OR 11.9, 95% CI 6.6 to 20.8). The POST group had more antibiotic days per total neutropenia days (0.76 PRE vs 0.97 POST, P < 0.0001), but the frequency of first-episode C. difficile infection was not significantly different between groups (OR 0.36, 95% CI 0.1 to 1.4). Conclusion: Universal cefepime prophylaxis for children with AML and chemotherapy-induced neutropenia was associated with a significant reduction in the incidence of febrile neutropenia and neutropenia-associated BSIs without increasing the incidence of C. difficile infection. Disclosures: All Authors : No reported disclosures